Preferences for Delivering Brief Alcohol Intervention to Risky Drinking Parents in Children's Social Care: A Discrete Choice Experiment. (21st April 2022) - McGovern, R; Homer, T; Kaner, E; Smart, D; Ternent, L
Abstract: Aims: Many parents in contact with children's social care services misuse alcohol however do not meet the threshold for specialist alcohol treatment, and typically do not receive appropriate support for their needs. Brief alcohol interventions have been found to be effective in healthcare settings, however, it is unknown whether the brief intervention structure delivered within health settings would transfer well into children's social care. This paper aims to examine the characteristics of brief intervention for alcohol misusing parents which social care practitioners consider to be important and acceptable to implement in this sector. Methods: We assessed preferences for, and acceptability of, brief alcohol intervention with parents in contact with children's social care using a discrete choice experiment. We recruited 205 children's social care practitioners from London and the North East of England. Data were analysed using mixed logit which accounted for repeated responses. Findings: Six attributes showed statistically significant coefficients, suggesting that a brief intervention with these attributes would encourage implementation. These were: level of alcohol-related risk targeted; intervention recipient; timing of intervention; duration of sessions; number of sessions and intervention structure. The attribute of most importance identified based on the attribute with the largest coefficient in the conditional logit model was risk level. Conclusions: Brief alcohol interventions delivered to parents in social care should focus on the impact upon children and the wider family, they should be a flexible part of on-going casework and should be more intensive and less structured. Abstract : Short Summary: BAIs in health settings typically following universal screening, are delivered in a single session and provide simple structured advice. In children's social care BAIs need to be targeted at parents whose alcohol use is causing observable problems within the family and should be more intensive and less structured.